A High-Quality Reference Genome Sequence and Genetic Transformation System of Aralia elata - Liu, Wenxuan; Guo, Wenhua; Chen, Song; Xu, Honghao; Zhao, Yue; Chen, Su; You, Xiangling (Frontiers in Plant Science, 2022)
Aralia elata, a perennial woody of the genus Aralia in the family Araliaceae. It is rich in saponins and therefore has a wide range of pharmacological effects. Here, we report a high-quality reference genome of A. elata, with a genome size of 1.21 Gb and a contig N50 of 51.34 Mb, produced by PacBio HiFi sequencing technology. This is the first genome assembly for the genus Aralia. Through genome evolution analysis, we explored phylogenetic and whole-genome duplication events. Evolutionary analysis showed that a recent whole genome duplication event occurred in A. elata before it diverged from Araliaceae. By analyzing the genome sequence of A. elata and combining the transcriptome data from three tissues, we discovered important genes related to triterpene saponins biosynthesis. Furthermore, based on the embryonic callus induction system of A. elata established in our laboratory, we set up the gene transformation system of this plant. The genome genetic information and genetically modified system obtained in this study provides insights into A. elata and lays the foundation for further exploration of the A. elata regulatory mechanism.